Management of inheritance property in Selangor / Nurzafira Zainul Abidin and Nur Afiqah Jahari - Zainul Abidin, Nurzafira; Jahari, Nur Afiqah (Center for Islamic Philantrophy & Social Finance (CIPSF), 2022)
In Islam, every property or piece of land left by a deceased proprietor must be immediately managed by heirs. It is known as inheritance property, and it will be managed by the agencies concerned. In Islamic terminology, real estate is referred to as al-ard, al-'aqar, or ghoirul manqul, meaning immovable property. Every country faces unique obstacles in handling inherited property, and most people have issues that cause delays in the process of distributing legacy property. It is because, in terms of economics, land has worth that can contribute to any state's economy around the world. As for Malaysian land cases, it must refer to their respective Act depending on the type, case, or situation. The objectives of this paper are to explore the distribution and process of inheritance property and determine each role of agencies involved in managing inheritance property by using semi-structured interview. This paper will be useful enhancing the understanding of inheritance property management by the agencies involved.